Gustavo Garza (comp.). Una década de planeación urbano-regional en México, 1978 1988. México : El Colegio de México, 1989. 486 p. - García Col, Julio (Estudios Demográficos y Urbanos, 1990)
GUSTAVO GARZA (comp.), Una década de planeación urbano-regional en México, 1978-1988, El Colegio de México, México, 1989.